PROGRAM KOMUNIKASI PEMASARAN UNTUK MENINGKATKAN REVENUE F&B 11/12 ROOFTOP BAR SEMARANG SEBAGAI EVENT MANAGER - Nisrina Sephiare; Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The food and beverage (F&B) industry continues to grow and contributes significantlyto Indonesia’s economy. However, 11/12 Rooftop Bar Semarang experienced fluctuatingrevenue and failed to meet its sales targets compared to the previous year. This study aims toanalyze the implementation of a marketing communication program to increase F&B revenuethrough event-based strategies. This study applies the Integrated Marketing Communication(IMC) Mix approach, integrating advertising, social media marketing, public relations, directmarketing, event marketing, and sales promotion. The programs implemented include KorokkeHalloween Night, After Track, Sunset Rooftop Yoga, and promotional strategies such as Buy 1Get 1 and KTM 10%. The results show that the program successfully increased revenue by7.26%, exceeding the initial target of 7.02%. The Event Manager played a significant role inplanning, coordinating, and executing the programs effectively. The success of the program isreflected in the achievement of Key Performance Indicators (KPI) for each event.